The scope of EIA in Ukraine – scientific priorities of the professor Yaroslav Adamenko - Kundelska, Tamara (Lviv Politechnic Publishing House, 2017)
The article describes the stages of professional formation and scientific priorities of Professor Yaroslav Adamenko. The main results of joint research with students on the procedure for assessing the environmental impact of technogenic-dangerous objects, as well as ecological assessment of urbosystems and hydro ecosystems are given. The following is a description of the main scientific research results and possibilities for their practical application.
Keywords: scientific research; EIA; environmental safety; generalization of alternatives; environmental assessment procedure